Rare and complex diseases in focus: ChatGPT's role in improving diagnosis and treatment - Zheng, Yue; Sun, Xu; Feng, Baijie; Kang, Kai; Yang, Yuqi; Zhao, Ailin; Wu, Yijun (Frontiers in Artificial Intelligence, 2024)
Rare and complex diseases pose significant challenges to both patients and healthcare providers.These conditions often present with atypical symptoms, making diagnosis and treatment a formidable task. In recent years, artificial intelligence and natural language processing technologies have shown great promise in assisting medical professionals in diagnosing and managing such conditions. This paper explores the role of ChatGPT, an advanced artificial intelligence model, in improving the diagnosis and treatment of rare and complex diseases. By analyzing its potential applications, limitations, and ethical considerations, we demonstrate how ChatGPT can contribute to better patient outcomes and enhance the healthcare system's overall effectiveness.